STRENGTHENING THE ISLAMIC AQIDAH OF TAKMIR MOSQUE AS AN ANTIDOTE TO THE ANTI-PANCASILA ISLAMIC IDEOLOGY - Huda, H. Syamsul; Permata, Bagus Andrian; Ahid, H. Nur; Muafiah, Evi (CENTRAL ASIA AND THE CAUCASUS, 2021)
Referring to the essential function of a mosque which is not only a place of worship but also a function of preaching in building civilization in society and looking at the facts and phenomena of some current mosques that are not well managed, it is not surprising that the existence of mosques that should be used as strategic places in building unity and the integrity of the ummah has instead shifted its function to become a center for fundamentalist Islamic preaching which leads to intolerance, radicalism and anti-Pancasila. The spread of anti- Pancasila Islamic teachings in Indonesia is increasingly structured and massive through religious institutions, information technology facilities and religious facilities such as mosques, prayer rooms and majlis ta'lim. The purpose of this research is that researchers want to provide intensive assistance to mosque takmir administrators in housing estates in Kediri City as an effort to counteract the spread of anti-Pancasila Islamic ideology which often leads to intolerance, division and even radicalism. This research uses qualitative data collection methods, and because the researcher acts as a facilitator or companion, the process of extracting data uses participatory research. This method is used because the entire process of community service activities involves community participation. The results showed that strengthening faith can reduce the influence of anti-Pancasila ideology. In addition, strengthening Islamic creed based on gathering with pious people can also strengthen ties of friendship, faith, and understanding of Islamic religious knowledge.